Edukasi Tentang Pengaruh Teknologi Komunikasi Terhadap Siswa Siswi SMA Negeri 1 Lengayang - Delpa, Delpa; Fitri, Wahyu; Asmul, Ali (CV. ITTC INDONESIA, 2024)
Basically, social media can be used to be oriented towards positive things. However, many gadget users do not maximize the use of social media based on positive values. In fact, many young people, especially female students, are being carried away by advances in communication technology media. It is also not uncommon for some of them not to use gadgets as a medium in the learning process and it is also not uncommon for the next generation to not recognize traditions as their own ancestral heritage. What is even more worrying is that many teenagers today tend to use social media based on online games and it is not uncommon for them to encounter the ITE Law. Basically, they as the younger generation are the hope for their parents, nation and state. The low awareness of gadget users among the younger generation uses social media that is positively oriented, such as their involvement in posts that can contribute to the promotion of their own traditions and culture. Starting from this problem, we from the Communication Science Study Program community service team will carry out Community Service from the Communication Science Study Program, Faculty of Business Economics and Social Sciences to Lengayang 1 Public High School, Pesisir Selatan Regency. The aim of this activity is to educate about the importance of using social media oriented towards positive things such as the learning process and maintaining traditions. This activity method uses the lecture method when carrying out Community Service activities. The method for collecting data uses in-depth interview methods (Interview in-Depth) with study informants. In addition, the data collection method also used filling out questionnaires for 200 grade 3 students of SMAN 1 Lengayang. The study concluded that students at SMA 1 Lengayang lacked awareness of using media as a medium to improve and promote their own culture and traditions, so it was necessary to involve students in promotional events in using gadgets as a source of teaching materials and as an opportunity to introduce and promote culture as an approach to empowering traditions in the media. on line